2019
DOI: 10.3393/ac.2018.08.28
|View full text |Cite
|
Sign up to set email alerts
|

Early Systemic Failure After Preoperative Chemoradiotherapy for the Treatment of Patients With Rectal Cancer

Abstract: Purpose Distant metastasis can occur early after neoadjuvant chemoradiotherapy (CRT) in patients with rectal cancer. This study was conducted to evaluate the clinical characteristics of patients who developed early systemic failure. Methods The patients who underwent neoadjuvant CRT for a rectal adenocarcinoma between June 2007 and July 2015 were included in this study. Patients who developed distant metastasis within 6 months after CRT were identified. We compared shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This is a very small number that suggests that metastases after CRT may be a rare entity. This result is consistent with those reported by Choi et al [16], who conducted a study for early metastases on 107 patients who received preoperative CRT and only 7 (6.5%) patients developed metastases during the waiting period.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is a very small number that suggests that metastases after CRT may be a rare entity. This result is consistent with those reported by Choi et al [16], who conducted a study for early metastases on 107 patients who received preoperative CRT and only 7 (6.5%) patients developed metastases during the waiting period.…”
Section: Discussionsupporting
confidence: 93%
“…To date, multiple questions have been asked about patients who will not respond to preoperative CRT and who will develop early metastases either during or after completion of treatment [ 16 ]. Therefore, from a practical point of view, changing the chemotherapy regimen and/or radiation treatment dose with a short and meticulous follow-up period may help in detecting non-responders early and give a chance to modify the treatment protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al reported this issue. 18 Patients who developed distant metastases within 6 months after CRT were identified. The indications for preoperative LCRT were T4, CRM involved or threatened, or suggestive metastasis of a lateral pelvic lymph node (LN), defined as an LN beyond the TME plane such as iliac and obturator LNs, on initial staging.…”
Section: Cancer Progression At the Time Of Restaging After Completion...mentioning
confidence: 99%
“…To date, there have been few reports on this issue because of the small number of patients. Choi et al reported this issue 18 . Patients who developed distant metastases within 6 months after CRT were identified.…”
Section: Challenging Issuesmentioning
confidence: 99%